2013
DOI: 10.3390/molecules180910639
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Constituents and Antioxidant Activity of Peel, Flowers and Leaf Oils of Citrus aurantium L. Growing in Greece

Abstract: Abstract:The volatile constituents of the essential oils of the peel, flower (neroli) and leaves (petitgrain) of bitter orange (Citrus aurantium L.) growing in Greece were studied by GC-MS. The analytical procedures enabled the quantitative determination of 31 components. More specifically, the components of the essential oils identified were: twelve in the peel, twenty-six in the flowers, and twenty and sixteen in old and young leaves, respectively. The major constituents of the different parts of Citrus aura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
105
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(130 citation statements)
references
References 20 publications
13
105
0
12
Order By: Relevance
“…[13,14] These results are comparable to results obtained from the other studies on DPPH scavenging ability of bitter orange peel oil. [15] …”
Section: Resultsmentioning
confidence: 99%
“…[13,14] These results are comparable to results obtained from the other studies on DPPH scavenging ability of bitter orange peel oil. [15] …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the amount of limonene in bitter orange peel essential oils is in majority (2,(13)(14)18). Moreover, Sarrow et al (2013) reported that limonene (94.67%), myrcene (2%) and linalool (0.67%) were the main components of bitter orange ripe peel essential oil, grown in Greece.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Sarrow et al (2013) reported that limonene (94.67%), myrcene (2%) and linalool (0.67%) were the main components of bitter orange ripe peel essential oil, grown in Greece.…”
Section: Discussionmentioning
confidence: 99%
“…The oils obtained from its fruits (peels), flowers, and leaves have different chemical compositions. The first are rich in limonene whereas the flower and leaf oils are characterized by different quantities of linalool and linalyl acetate (Sarrou et al 2013). Also, a close relationship between ontogenesis and oil composition can be seen in several species.…”
Section: Important Trade Essential Oilsmentioning
confidence: 99%